Perspectives on religious landscape in Africa - Acquah, Lady Jane; Falola, Toyin 1953- (Carolina Academic Press, 2020)
"This book brings together several chapters presented at the thirteenth annual Africa Conference convened by Toyin Falola at the University of Texas at Austin, and coordinated by Lady Jane Acquah and Ryan Groves, in 2013. The chapters here cover a range of research topics on religion and its social, economic, and political interplay within sub-Saharan African societies, especially in countries such as Burkina Faso, Ghana, Nigeria, Cameroon, South Africa, and Mali. This text presents a variety of research information on religious influences including political changes, politicization of Islam, migration of people, the spread of religious ideas, education, and terrorism"--
Keywords: Politik; Gesellschaft; Religion; Subsaharisches Afrika; Africa, Sub-Saharan / Religion / Congresses; Sub-Saharan Africa; Conference papers and proceedings; Konferenzschrift -- 2013 -- Austin, Tex.